The simultaneous exposure to heat and whole-body vibration on some motor skill functions of city taxi drivers - Aghamiri, Seyed Zahra; Aliabadi, Mohsen; Farhadian, Maryam; Golmohammadi, Rostam; Shafiee Motlagh, Masoud (La Medicina del Lavoro, 2022)
Background: Driving requires sensory-motor abilities in unpredictable and complex driving scenarios. This experimental study aimed to investigate the combined effects of exposure to whole-body vibration and heat on motor skill functions of city taxi drivers. Methods: This study was conducted using a driving simulator on 30 male taxi drivers. The drivers were exposed to five exposure conditions set by a single or combined exposure of two air temperatures (24 and 30 °C) and two vibration levels (0.5, 1 m/s2). Motor skill functions, including body balance, hand grip strength, and perceived fatigue, were measured using a force plate, dynamometer, and Borg CR-10 questionnaire. Results: The separate exposure to heat did not modify balance and hand grip strength, but its combined exposure to vibration affected balance and grip strength. The effect sizes of heat, vibration, and heat + vibration on balance were respectively 0.003, 0.23, and 0.441. Vibration exposure made the most significant mean differences in hand grip strength compared with the other scenarios. The separate effect of heat on drivers’ perceived fatigue was comparable to vibration. The combined exposure to heat and vibration aggravated the perceived fatigue associated with exposure to heat and vibration alone. Conclusion: Vibration mainly affects the driver’s postural equilibrium, handgrip strength, and fatigue. The heat exposure alone did not have any remarkable effects on the balance responses and handgrip strength; however, it significantly increased the drivers’ perceived fatigue. Exposure to heat can aggravate the effects of vibration on motor skills with a synergistic interaction.